Meaningful occupations of young adults with muscular dystrophy and other neuromuscular disorders. (October 2019) - Lindsay, Sally; Cagliostro, Elaine; McAdam, Laura
Background: Youth with Duchenne muscular dystrophy (DMD) and other neuromuscular disorders are living well into adulthood and often need help engaging in meaningful occupations. Purpose: Our purpose was to explore enablers and barriers to engaging in meaningful occupations, from the perspectives of youth, parents, and practitioners. Method: This qualitative study involved 26 participants (11 parents, eight youth ages 19 to 28 [mean = 22.3 years], seven practitioners). Data were obtained from semistructured interviews and analyzed using an interpretive descriptive approach. Findings: Youth with DMD and neuromuscular disorders engage in meaningful occupations in a variety of ways. Occupational enablers were supports and accommodations and self-care skills and coping strategies, while occupational barriers involved societal expectations of a normative adulthood, discrimination and inaccessible environments, lack of supports and resources, medical challenges, fatigue, lack of motivation, and social isolation and depression. Implications: Practitioners should work to uncover what youth consider important and connect them to appropriate resources so they can engage in meaningful occupations.